Maxillary First Molar with Three Mesiobuccal Root Canals: A Case Report - Laila A. Bahammam (Journal of King Abdulaziz University: Medical Sciences, 2023)
A case report to present the endodontic management and the follow up of a maxillary first molar with three mesiobuccal canals with separate orifices and apical foramina (Vertucci Type VIII). Root canal treatment was provided, final restoration was accomplished and reevaluation was performed. The results of this case report revealed a successful endodontic treatment, and that treating extra canals in maxillary first molars is challenging due to the difficulty in locating and managing it. This often leads to endodontic failures due to the residual bacteria that are present inside the missed canals. Complete clinical and radiographic examination and a thorough knowledge of the morphology of teeth are necessary for successful clinical results.